1972
DOI: 10.1021/ja00778a069
|View full text |Cite
|
Sign up to set email alerts
|

Nicandrenone, an insecticidal plant steroid derivative with ring D aromatic

Abstract: Though in enzymatic reactions nicotinamide-adenine dinucleotide (NADH) serves as a reducing agent for aldehydes, via direct hydrogen transfer, rather extensive search has led to no aldehyde substrate reducible by 1.4-dihydropyridine in simple model systems operating in aqueous solution at ambient temperature.1 For horse liver alcohol dehydrogenase the Zn11 species present at each of the two NADH-containing active sites has been suggested to facilitate aldehyde reduction by polarization of the carbonyl group th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…8a,17a (80,84,88,91) Nicandrenolactone ( = Nic-l lactone) (190) 8a (92) Salpichrolide A (191) 10a (159) F. Jaborols (Ring A Aromatic Withanolides and Precursor) laborol (192) 6d (72,75) laborosalactone Q (193) 6c…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…8a,17a (80,84,88,91) Nicandrenolactone ( = Nic-l lactone) (190) 8a (92) Salpichrolide A (191) 10a (159) F. Jaborols (Ring A Aromatic Withanolides and Precursor) laborol (192) 6d (72,75) laborosalactone Q (193) 6c…”
Section: Namementioning
confidence: 99%
“…The insect repellent and insecticidal properties of nicandrenone (189) and the insect antifeedant property of withanolide E (150) and of a number of related natural and synthetically modified withanolides have been studied (13,84,94,254). Further investigation of this property of withasteroids is expected to yield fruitful results.…”
Section: Biological Activity Of Withasteroidsmentioning
confidence: 99%
“…From this species, several withanolides have been reported possessing either the normal or modified skeletons (ring-D aromatic). [6][7][8][9][10][11][12] N. physalodes is considered an ornamental plant possessing insect repellent properties. In fact, its main constituent named as nicandrenone showed antifeedant activity.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8]13 In a continuing effort to isolate active compounds from the Brazilian Solanaceae, the acetone extract from N. physalodes was investigated. As results, five new withanolides (15-oxonicaphysalin B (1), 6β,7α-dihydroxynicandrenone 10 (2), 24α ,25β -dihydroxy-nicandrenone-2 (3 ) and a mixture of the epimers 17-(1α/1β-methylpropanone)-nicandrenone (4a/4b)), in addition to nicandrenone-10 (5), nicandrenone (6), nicandrenone-7 (7), 10 nicandrenone-2 (8), 7 nicaphysalin B (9), 9 and 26R-withahisolide G (10), 12 were isolated. The isolated compounds were evaluated for their antibacterial and antifungal effects.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Previous studies have shown that the steroidal lactones (withanolides and physalins) exhibit a range of biological activities, including anti-tumor, 3) immunomodulatory, 4) antimycobacterial, 5) anti-fungal, anti-inflammatory, 6,7) insect repellant, 8) and immunostimulating properties. 9) Compound 1 has also shown moderate cytotoxic activity against HeLa cells.…”
mentioning
confidence: 99%